Implementation of a novel communication tool and its effect on patient comprehension of care and satisfaction. Issue 5 (25th May 2012) - Simmons, Stefanie Anne; Sharp, Brian; Fowler, Jennifer; Singal, Bonita
Abstract : Background: Emergency department (ED) communication has been demonstrated as requiring improvement and ED patients have repeatedly demonstrated poor comprehension of the care they receive. Through patient focus groups, the authors developed a novel tool designed to improve communication and patient comprehension. Study design: This is a prospective, randomised controlled clinical trial to test the efficacy of a novel, patient-centred communication tool. Patients in a small community hospital ED were randomised to receive the instrument, which was utilised by the entire ED care team and served as a checklist or guide to the patients' ED stay. At the end of the ED stay, patients completed a survey of their comprehension of the care and a communication assessment tool-team survey (a validated instrument to assess satisfaction with communication). Three blinded chart reviewers scored patients' comprehension of their ED care as concordant, partially concordant or discordant with charted care. The authors tested whether there was a difference in satisfaction using a two-sample t test and a difference in comprehension using ordinal logistic regression analysis. Results: 146 patients were enrolled in the study with 72 randomised to receive the communication instrument. There was no significant difference between groups in comprehension (OR=0.65, 95% CI 0.34 to 1.23, p=0.18) or communication assessment tool-team scores (difference=0.2, 95% CI: −3.4 to 3.8, p=0.91). Conclusions: Using their novel communication tool, the authors were not able to show a statistically significant improvement in either comprehension or satisfaction, though a tendency towards improved comprehension was seen.